Supreme Court Impacts in Public Health Law: 2021-2022. Issue 3 (2022) - Hodge, James G.; White, Erica N.; Freed, Rebecca; Wells, Nora
Abstract: In a dynamic term of the United States Supreme Court in 2021-2022 a series of critical cases raise manifold changes and impacts on individual and communal health through 10 key areas ranging from abortions to vaccinations.